Turkish politics and the rise of the AKP : dilemmas of institutionalization and leadership strategy - Kumbaracibasi, Arda Can (Routledge studies in Middle Eastern politics., 2009)
The Justice and Development Party (AKP) has been in power since 2002. This book charts the rise and development of the most successful party with an Islamic background in the history of the Turkish Republic party from its roots through to government, analysing in particular its internal organisation and dynamics.